Reducing Disruption from Subtle Information Delivery during a Conversation: Mode and Bandwidth Investigation - Ofek, Eyal; Iqbal, Shamsi; Strauss, Karin (Sig Chi 2013 Human Factors in Computing Systems, 2013)
With proliferation of mobile devices that provide ubiqui-tous access to information, the question arises of how dis-tracting processing information in social settings can be, especially during face-to-face conversations. However, relevant information presented at opportune moments may help enhance conversation quality. In this paper, we study how much information users can consume during a conversation and what information delivery mode, via audio or visual aids, helps them effectively conceal the fact that they are receiving information. We observe that users can internalize more information while still disguising this fact the best when information is delivered visually in batches (multiple pieces of information at a time) and per-form better on both dimensions if information is delivered while they are not speaking. Interestingly, participants qualitatively did not prefer this mode as being the easiest to use, preferring modes that displayed one piece of infor-mation at a time.